Bodies as Evidence Security, Knowledge, and Power - Maguire, Mark; Rao, Ursula; Zurawski, Nils (Global Insecurities, 2018)
From biometrics to predictive policing, contemporary security relies on sophisticated scientific evidence-gathering and knowledge-making focused on the human body. Bringing together new anthropological perspectives on the complexities of security in the present moment, the contributors to Bodies as Evidence reveal how bodies have become critical sources of evidence that is organized and deployed to classify, recognize, and manage human life. Through global case studies that explore biometric identification, border control, forensics, predictive policing, and counterterrorism, the contributors show how security discourses and practices that target the body contribute to new configurations of knowledge and power. At the same time, margins of error, unreliable technologies, and a growing suspicion of scientific evidence in a "post-truth" era contribute to growing insecurity, especially among marginalized populations.